The Effect of Work Engagement on the Performance of Generation Z Employees - Fatimah Az'zahra; Annisa Warastri (unprimdn.ac.id, 2026)
The purpose of this study is to determine the impact of Work Engagement on the productivity of millennial and Gen Z workers. This study is quantitative and uses a descriptive correlational strategy. The purpose of this data collection is to examine the relationship between research variables. There were 96 respondents from Generation Z (those aged between 18 and 28 years) who filled out the questionnaire used to collect data. The data were analyzed using basic linear regression. With a significance value of 0.000 (<0.05) and a coefficient of determination of 54.9%, the analysis shows that when the level of employee engagement increases, performance also increases. It can be concluded that the correlation between Work Engagement and performance is linear. This study strengthens the idea that the level of engagement of Gen Z workers with their work is directly correlated with their productivity in the current workplace. Therefore, efforts to increase the productivity of Generation Z workers must consider their level of engagement in the workplace.